Efeitos da prática regular da atividade física sobre a função pulmonar no contexto do estresse crônico relacionado ao trabalho - (:unkn) unknown (Universidade Brasil, 2022)
Circadian rhythm changes negatively impact several aspects of health, including lung function. The chronic shift work scale classically induces changes in circadian rhythm. On the other hand, regular physical activity is able to improve and preserve lung function. In this sense, although it has already been shown that military policeofficers working on an alternate shift schedule present alterations in lung function, itis not known how much regular physical activity is able to preserve or prevent thedecline of lung function in this population, what is the purpose of this project. In thiscontext, military police officers(n=25;38.73±6.92 years) who work on a 12 x24hour and 12 x 48 hour non-physically active work scale will be evaluated incomparison with military police officers (n=25;32.92±5.87 years) who work on a 12 x 24-hour work scale and 12 x 48 hours who engage in physical activity. The parameters evaluated will be: lung function and pulmonary mechanics. Statisticalanalysis and graphics will be performed using the Graphpad Prism 5.0 softwares. Theunpaired Student t test will be used for comparison between groups. The value ofp≤0.05 will be considered as statistically different.
Keywords: Estresse; Função pulmonar; Mecânica pulmonar; Atividade física; Engenharia Biomédica; Bioengenharia